Perancangan media informasi Program Studi - Abdul Aziz Said; Baso Indra Wijaya Aziz (Seminar Nasional LP2M UNM, 2019)
This study aims to create an information media containing a comprehensive explanation of the existence of study programs within the Faculty of Arts and Design Makassar State University, where the final product is in the form of information media in motion picture format recorded on DVD discs. The methodology applied is 'design research methodology' which includes three stages, namely: analysis, synthesis, and evaluation. In the analysis process which is the pre-production stage, problem identification is carried out, story board analysis, and identification of the main factors related to the methods and techniques of making information media. In the synthesis process which is the production stage, a video recording is carried out about the existence of each study program in the form of sequential moving images, image/video editing, and sound/background music input, which are then compiled in a single information media unit. While at the post-production stage is the final evaluation stage by verifying based on the problem and the purpose of the research and improvement. The benefits of this study are to provide a true and comprehensive understanding to the wider community, about the existence of the Study Program: Fine Arts Education, Physical Education, Dance, and Visual Communication Design; with the hope of increasing interest and interest in the community to become students at one of the study programs.